National Identity, Historical Consciousness, and Historical Preservation - Thompson, Tracey L.; Dean, Kenyetta T. (International Journal of Bahamian Studies, 2017)
Bahamians are a people of increasing heterogeneity. The experiences of Bahamians of all backgrounds would profit from greater scholarly exploration. In any such undertaking, utilizing extant “hidden” archival collections and capturing oral history narratives is essential, as the challenge of documenting the historical experience of the African-descended Anglophone majority of Bahamians makes plain. Libraries can play a leading role in reducing the risk of losing hidden collections and oral narratives. That much is clear from the investment that the University Libraries of the University of The Bahamas have made in hosting “From Dat Time”: The Oral & Public History Institute of the University. Collaboration among cultural heritage institutions can accelerate the pace of bringing hidden collections to light and generating oral narratives. Technological advances enable us, meanwhile, to offer broad access to disinterred collections and captured oral history narratives. We can develop models of accessing such data that strike the right balance among competing imperatives of fostering education and research, of generating revenue, and of strengthening national heritage institutions.